Pelayanan Sosial dan Keagamaan Dengan Menggunakan Media Audio Visual Dalam Meningkatkan WPKNS ABH di Lembaga Permasyarakatan Kelas II A Curup - Fadila Fadila; Eka Yanuarti (Islamic Counseling : Jurnal Bimbingan dan Konseling Islam, 2019)
The article is the result of actions taken in research to improve the WPKNS ABH. The method used in this paper is descriptive analysis, by presenting the results of the study and analyzing the results obtained in the study. The WPKNS ABH is giving donations to Curup Class II Lapas. By coordinating with the Lapas and Stakeholders, in the form of Islamic material, general education material, soft skills, national knowledge and insights, providing counseling services and holding an Islamic Competition. The results of the study and actions showed the insight, knowledge, skills, values and attitudes of the ABH in Class II A Curup Prison, before and after the action: ABH insights increased by 52.5% from the total score before the action amounted to 28 (35%) increased to a total of 75 (87.5%) after the action. ABH's knowledge increased by 41.25%, the overall total score before carrying out the actions amounted to 62 (38.75%) increased to 128 (80%) after the action. ABH's skills experienced an increase of 52.5% from a total score of 28 (35%) before the action became 75 (87.5%) after the action was taken. The aspect of ABH value increased by 58.75% from the initial total score of 26 (32.5%) to 73 (91.25%) after the action was taken. The attitude aspect of ABH increased by 43.75% from the total score of 35 (43.75%) to 75 (87.5%) after the action was taken.